An Audit of Maternal and Child Health Services in Low-Resource Settings: Utilization Patterns and Service Delivery Gaps - Syeda Fatima Rizvi, Saira Kiran, Saleem Adil, Amber Rehman, Jarin Tasnim, Hafsa Imran Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
In low-resource settings, persistent gaps in maternal and child health service deliveryundermine efforts to improve outcomes. This study aimed to audit utilisation patterns of maternal and child health services and